ANEMIA PADA GAGAL JANTUNG - Hendrata, Cecilia; Lefrandt, Reginald L. (JURNAL BIOMEDIK : JBM, 2010)
Abstract: Anemia, a frequently occuring comorbid in patients with heart failure, is increasingly recognized as an independent predictor of morbidity and mortality. The etiology of anemia associated with heart failure is not entirely understood. It is assumed as a multifactorial anemia, most likely caused by chronic kidney diseases and other chronic diseases. Besides that, iron deficiency due to lack of iron intake and absorption, and chronic blood loss due to anti-platelet agents play some important roles, too. Other factors related to risks of anemia in heart failure are old age, female gender, decrease of body mass index, usage of angiotensin converting enzyme inhibitors (ACE-inhibitors) and angiotensin receptor blockers (ARBs), and advanced heart failure.  Based on its documented impact on clinical outcomes, anemia has emerged as a possible target for treatment in patients with heart failure. Further studies are needed to determine the optimal threshold for initiation of treatment, target hemoglobin, optimum dosing regimen, choices of erythropoietic agents, roles of iron suplementation, and long-term safety of erythropoietic agents in anemic patients with heart failures. Key words: anemia, heart failure, management, therapy.     Abstrak: Anemia merupakan komorbid yang sering ditemukan pada penderita gagal jantung dan telah dikenal sebagai prediktor independen dari morbiditas dan mortalitas. Penyebab anemia yang menyertai gagal jantung tidak sepenuhnya diketahui, diduga sebagai anemia multifaktor yang umumnya diakibatkan oleh gagal ginjal kronis dan penyakit kronis lainnya. Selain itu defisiensi besi akibat kurangnya asupan maupun absorbsi besi, serta kehilangan darah kronik akibat konsumsi obat-obatan anti platelet turut berperan. Faktor lainnya yang berhubungan dengan resiko terjadinya anemia pada gagal jantung adalah: usia tua, jenis kelamin perempuan, adanya  penurunan indeks massa tubuh, penggunaan obat-obat angiotensin converting enzyme inhibitors (ACE-inhibitors) dan angiotensin receptor blockers (ARBs), serta gagal jantung tingkat lanjut. Berdasarkan dampaknya terhadap hasil klinis, anemia perlu dipikirkan sebagai target pengobatan pada penderita gagal jantung. Studi lanjut diperlukan untuk menentukan ambang optimal untuk memulai pengobatan anemia, hemoglobin target, regimen dosis yang optimum, pemilihan preparat eritropoietik, peran suplementasi besi, dan keamanan pemberian jangka panjang preparat eritropoietik pada penderita anemia dengan gagal jantung. Kata kunci: anemia, gagal jantung, penanganan, pengobatan.